INTEGRATING INTERTEXTUAL AND COMMUNITY RESPONSE ANALYTICAL LENSES TO TURN SYAIR CENDAWAN PUTIH’S A CHILDREN'S STORY “THE ADVENTURE OF CENDAWAN PUTIH” INTO A SCIENCE LEARNING - Nurhayati, Nurhayati; Nadya, Nyayu Lulu; Shilviany, Sary; Nuzula, Khalidatun; Bujaya, Muhammad; Sucini, Emelia; Budiyanto, Darmawan (LPPM Universitas Jambi, 2024)
This study explores the transformation of the Cendawan Putih poem into prose suitable for children's science learning, examining the adaptation process and public perception. Using a qualitative approach, the study employs intertextual theory to analyze textual transformations such as expansion, conversion, modification, and citation and community response theory to capture stakeholders’ views. The research investigates how the Cendawan Putih poem has been creatively adapted into the children’s story The Adventure of Cendawan Putih to enhance science learning while maintaining cultural and educational value. The findings reveal that adapting Cendawan Putih for children’s literature not only preserves core narrative elements but also integrates science concepts relevant to young readers. The adaptation utilizes techniques such as expansion and modification, enriching the original storyline to highlight nature, ecosystems, and environmental science in an accessible format for children. Public feedback, collected through Focus Group Discussions (FGDs) with cultural figures, educators, academics, and youth, shows broad support for this transformation. Stakeholders emphasize the story’s potential to foster cultural awareness and introduce foundational science concepts, making it an innovative tool for learning. This study highlights how traditional literary forms can be reimagined for children’s science learning, merging cultural heritage with modern educational needs. By presenting Cendawan Putih in a format that supports both cultural preservation and science education, this work positions the story as an intergenerational bridge and a valuable addition to literature-based science learning. It underscores the importance of community involvement in literary adaptation, providing new insights for literature, cultural education, and science pedagogy.